Reproductive Factors and Serum Uric Acid Levels in Females from the General Population: The KORA F4 Study - Stöckl, Doris; Döring, Angela; Thorand, Barbara; Heier, Margit; Belcredi, Petra; Meisinger, Christa (PLOS ONE, 2012)
Objective Hyperuricemia is associated with an increased risk of metabolic and cardiovascular diseases. There are pronounced sex differences in the levels of uric acid. It is largely unknown whether or not reproductive parameters which induce hormonal changes are responsible for this. We examined if there are associations between reproductive parameters and uric acid levels in a female population-based sample. Methods In this cross-sectional analysis, data of 1530 women aged 32 to 81 years participating in the KORA F4 study, conducted between 2006 and 2008 in Southern Germany were used. Reproductive parameters were obtained by standardized interviews. Uric acid levels were tested by the uricase method. The whole study sample and stratified in pre- and postmenopausal women was analyzed. Results Menopausal status and earlier age at menarche were associated with higher serum uric acid levels (age-adjusted: p-values 0.003, <0.001 respectively; after multivariable adjustment, including BMI: p-values 0.002, 0.036). A history of oral contraceptive use showed an association with uric acid levels only after multivariable adjustment (p-value 0.009). Hot flushes showed an association with uric acid levels only after age-adjustment (p-value 0.038), but lost significance after adding other confounders. Other reproductive factors, including parity, current or ever use of hormone replacement therapy, current use of oral contraceptives, hysterectomy, bilateral oophorectomy, or depressive mood related to menopausal transition were not associated with uric acid levels. Conclusions Postmenopausal status, earlier age at menarche and a history of oral contraceptive use were independently associated with higher serum uric acid concentrations in women from the general population. Further studies, especially longitudinal population-based studies investigating the relationship of female reproductive parameters with uric acid levels are necessary to confirm our findings.